Support Networks among micro entrepreneurial women: comparison between Bangladesh, India and the Southern Mexico - Sato, Georgina; Cota, Rosario; Nolton, John (Mercados y Negocios, 2016)
Microcredit has been seen as a way of helping low-income people, primarily women, to survive, by giving them independence and the resources to create their own businesses. Low-income people have the support of social networks that allow their members to assist each other morally, economically and by sharing information. They also share experiences that make it easier to obtain the income needed for survival. Through their social networks and social capital the poor can use the tools provided by microcredits to improve their living conditions. This document compares the ways in which women in three countries associate, and use microcredits. The countries involved are India, Bangladesh and the South of Mexico.